Diseminasi Inovasi Media Pembelajaran Secara Online Dalam Mendukung Peningkatan Mutu PAI - Sulton Muzakki; Affan Ganesa Diadmaja; Agus Purwowidoodo; Zaini Fasya (Journal on Education, 2025)
This writing aims to identify innovations that can be made in the learning media of Islamic education subjects and the dissemination process of these innovations so that they can be used publicly through internet media. This research is of a qualitative type with a literature research model used in this writing technique. Literature research is research to seek, process, and analyze data sourced from documents, texts, manuscripts, and other written literacy materials to uncover the content of ideas and meanings that are implicitly or explicitly contained within them. The results of this study suggest that innovations in Islamic education learning media can use several options such as digital platforms, Islamic education learning applications, educational videos, Virtual Reality technology, games, podcasts, and audio recordings. Dissemination is the final process of innovation, which is a structured and planned process for spreading the results of the innovation that can be carried out directly or online. Online dissemination is used to address issues of time and flexibility in the dissemination process as well as to improve the quality of learning by providing innovative new media that can be accessed anytime and anywhere.